Guyana. Significant Achievements 2019 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The main activities carried out by the Institute in Guyana during 2019 are identified, with respect to the needs and interests of the country, strengthening pest control issues, such as the carambola fly, technology transfer, associated with climate-smart agriculture and climate resilience. Likewise, it contributed to the development of biotechnology standards, biosafety, policies, as well as support in health and food safety and the improvement of agricultural and livestock production systems. Finally, work was done to promote sustainable agrotourism, in the economic development and competitiveness of small agricultural companies, as well as in the development of rural territories.